Application of reflective papers in civil engineering education: a case study - Ena Kartina Abdul Rahman; S.K Rahman; Abdul Aziz Md Nor; Soon , Jiann Tan; Yok , Hoe Yap; El-Said, Mamdouh Mahmoud Zahran (World Institute for Engineering and Technology Education, 2019)
The purpose of this study was to investigate the effect of reflection on students' performance and assessment in civil engineering. In this study, the students in the final semester of a civil engineering programme were divided into two groups: the first group was tasked with writing a reflective paper, and the second group, a control group, was not required to write a reflective paper. Both groups were then assessed through a test based on the content of a lecture. The data were analysed in two parts. The first part comprised examination of the content of the reflective paper and its impact on students' performance. In the second part, the performance of both groups of students was compared. A research hypothesis was specified and tested. The hypothesis was tested through two independent samples t-test to determine whether there was a significant difference in the mean result between these two groups of students. The study revealed that the use of reflection in civil engineering education potentially could improve students' performance. (Abstract by authors)